Kiperin Mind Focus supplement mitigates chronic stress–induced neuroinflammation and molecular dysregulation and improves stress-related affective and exploratory behaviors in rats - Karcioglu Batur, Lutfiye; Yavas, Cuneyd; Kilic, Aysu; Dogan, Tunay; Yilmaz, Mert; Pektas, Ahsen; Demirci, Huri; Ustunova, Savas (Frontiers in Integrative Neuroscience, 2026)
BackgroundChronic stress is known to impair emotional regulation and adaptive behavioral responses through neuroinflammatory activation, oxidative imbalance, and dysregulation of neuroplasticity-related genes. Kiperin Mind Focus, a nootropic nutraceutical containing L-theanine, citicoline, phosphatidylserine, Rhodiola rosea, Ginkgo biloba, caffeine, and Lion’s Mane mushroom extract has been formulated to support stress resilience, mood regulation and neural health. This study aimed to investigate the neuroprotective and neuroregulatory effects of the combined formulation on behavioral, biochemical, histopathological, and molecular parameters in rats exposed to chronic unpredictable mild stress (CUMS).MethodsThirty-two adult male Wistar rats were randomized into four groups (n = 8): Control, Stress, Kiperin Mind Focus (MF), and Stress + Mind Focus (SMF). CUMS was applied for 45 days, and the combined formulation was administered by oral gavage (130 mg/kg/day). Behavioral outcomes were evaluated using the sucrose preference (SPT), open field (OFT), elevated plus maze (EPM), and forced swim (FST) tests. Serum and tissue cytokine levels (IL-1β, IL-6, IL-10, TNF-α) and oxidative stress index (TOS/TAS ratio) were measured. Hippocampal and prefrontal gene expression of FOS, DBH, NMB, BDNF, CREB1, GRIN2A, and GABRB1 was assessed via qPCR, and histopathological changes were semi-quantitatively scored.ResultsChronic stress induced anhedonia, anxiety-like behavior, and behavioral despair, accompanied by elevated proinflammatory cytokines, oxidative imbalance, and neuronal degeneration in the hippocampus and prefrontal cortex. The supplementation significantly improved SPT, OFT, EPM, and FST performance, normalized cytokine and oxidative parameters, and reduced neuronal injury scores. At the molecular level, supplementation attenuated stress-induced upregulation of FOS, DBH, and NMB while maintaining neurotrophic (BDNF, CREB1) and GABAergic (GABRB1) expression near control levels.ConclusionKiperin Mind Focus exerted robust neuroprotective, anti-inflammatory, and antioxidant effects under chronic stress, restoring molecular homeostasis and stabilizing stress-related behavioral outcomes. These findings support its role as a stress-buffering and mood-stabilizing supplement, that promotes emotional regulation and adaptive exploratory behavior under prolonged stress conditions.